An efficient secret key agreement protocol based on random noise without beacons. Issue 3 (2nd October 2019) - Guan, Albert
ABSTRACT: Computationally lightweight and unconditionally secure key agreement protocols are very useful for secure communication in public networks, especially for sensors with limited computing resources. In 2017, Guan and Tseng proposed a key agreement protocol which is computationally lightweight and unconditionally secure. In their protocol, it was assumed that the two communicating nodes can receive random bit string from a beacon node. Random bit string plays an important role in the generation of secret keys. With the advancement of hardware and software technologies, sensors may be able to generate good random strings. In this paper, we consider the case that the sensor nodes can generate random bit strings for secret keys. Therefore, no beacon nodes are required. The results of this study show that a key agreement protocol can be much more effective and efficient in the case that the communicating nodes can generate good random bit strings.